Current collector and preparation method thereof
Patent Information
- Application Number
- CN202411796163.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-06
Smart Images

Figure CN119481082A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a current collector and a preparation method thereof. Background Art
[0002] At present, current collectors based on polymer films have received widespread attention and application in the new energy industry. The preparation of this current collector usually uses the physical vapor deposition (PVD) method to deposit a layer of metal on a polymer film (such as polyester, polyolefin, etc.) to prepare a current collector with good conductivity. Compared with traditional current collectors, current collectors based on polymer films have the characteristics of low cost, light weight, and good internal insulation. These characteristics enable the current collector to reduce the cost of the battery when used in the battery, and improve the energy density and safety of the battery.
[0003] However, after the current collector is prepared, it will be further used to make pole pieces. In the process of preparing pole pieces, there are usually various processes such as rolling, which puts higher requirements on the mechanical properties of the current collector. The current collector prepared in the prior art is easily damaged during the preparation of the pole piece, has poor mechanical properties, and cannot meet the preparation process of the pole piece well.
[0004] In view of this, how to further improve the mechanical properties of the current collector to improve the stability in the process of preparing the electrode is of great significance for further improving the application and promotion of the current collector in batteries, and is also of great significance for further improving the performance of the battery. Summary of the invention
[0005] In order to solve the problems and shortcomings in the prior art, the present invention provides a current collector and a preparation method thereof, wherein the current collector has excellent mechanical properties, can improve the situation of surface defects of the current collector during the rolling process of the pole piece, and the current collector has good electrical conductivity. Therefore, the use of the current collector can be beneficial to further optimize the cycle charge and discharge performance of the battery.
[0006] According to a first aspect of the present invention, a current collector is provided, comprising a metal layer, at least a portion of the metal layer comprising staggered stacked metal grains, and an average length L of the metal grains in the Z direction and a thickness K of the metal layer satisfy the following relationship: 0<L≤0.8K; the Z direction is the direction of the thickness of the metal layer.
[0007] In the process of preparing battery pole pieces, in order to increase the unit capacity of the pole pieces, rollers are generally used to roll the pole pieces. During the rolling process, a large rolling pressure will be applied to the Z direction (perpendicular to the in-plane direction) of the pole piece, which puts higher requirements on the mechanical properties of the current collector in the Z direction. At present, the current collectors on the market are generally prepared by PVD (physical vapor deposition). The metal grains in the metal layer have a columnar crystal structure, the grains in the Z direction are large, and the mechanical properties are poor. Defects are easily generated during the rolling process, resulting in poor conductivity and reduced battery cycle life. Therefore, in order to further improve the mechanical properties of the current collector in the Z direction, it is necessary to develop a new current collector to promote the application and promotion of current collectors in batteries.
[0008] The present invention controls at least part of the metal layer in the current collector to contain staggered stacked metal grains, and the average length L of the metal grains in the Z direction and the thickness K of the metal layer satisfy the relationship 0<L≤0.8K. Firstly, this makes the average length L of at least part of the metal grains in the metal layer relatively small in the Z direction, which is smaller than the thickness of the metal layer, and can improve the overall anti-rolling ability of the metal layer, so that when it is rolled in the process of preparing the pole piece, it can have a higher pressure-bearing capacity. Even under a large rolling pressure, the current collector will not produce obvious structural defects or cracks, and can still maintain a high stability. Secondly, when these part of the staggered stacked metal grains are rolled in the process of preparing the pole piece, they can provide mutual support due to the mutual staggered stacking, thereby further improving the pressure-bearing capacity of the current collector, and further improving the overall pressure-bearing capacity of the pole piece, and optimizing the structural stability of the current collector and the pole piece.
[0009] The present invention is a metal grain structure with staggered stacking contained in at least part of the metal layer, which can be referred to in the present invention. Figure 1 The crystal planes of these dislocated and stacked metal grains are interconnected to form a continuous mesh structure. Therefore, the present invention effectively improves the overall stability of the pole piece and the battery by designing a metal layer with a special structure, so that during the charge and discharge cycle of the battery, the pole piece will not become unstable under cyclic stress due to structural defects of the current collector, thereby optimizing the cycle performance of the battery.
[0010] It should be noted here that in the present invention, the Z direction in the metal layer refers to the direction of the thickness of the metal layer, which is perpendicular to the direction of the plane of the metal layer. Therefore, the average length L of the grains in the Z direction in the metal layer refers to the average length of the grains in the thickness direction of the metal layer.
[0011] In addition, in the prior art, the average length L of the metal crystal grains in the metal layer in the Z direction is usually large, so the density of the metal layer is relatively poor, and thus the conductivity is relatively reduced. However, the present invention controls the average length L of the staggered stacked metal crystal particles in the Z direction contained in at least part of the metal layer of the current collector and the thickness K of the metal layer to satisfy the relationship 0<L≤0.8K, which makes the metal layer denser, which is beneficial to improving the conductivity of the current collector, and thus can further optimize the cycle charge and discharge performance of the battery.
[0012] Preferably, in the longitudinal section of the metal layer, at least a portion of the metal layer forms a staggered and stacked metal grain structure, and the grain boundaries between the metal grains together form a continuous network structure.
[0013] Preferably, in the cross section of the metal layer, at least a portion of the metal layer forms a staggered stacked metal grain structure, and the grain boundaries between the metal grains together form a continuous network structure.
[0014] Preferably, at least a portion of the metal layer is filled with the metal grains in the Z direction.
[0015] Preferably, the metal layer is composed of staggered stacked metal grains, the grain boundaries between the metal grains together form a continuous network structure, and the average length L of the metal grains in the Z direction and the thickness K of the metal layer satisfy the following relationship: 0<L≤0.8K; the Z direction is the direction of the thickness of the metal layer.
[0016] Preferably, in the longitudinal section of the metal layer, the area proportion of the staggered stacked metal grains in the metal layer is ≥20%. Ensuring that the area of the staggered stacked metal grains accounts for a certain proportion, that is, ensuring that the staggered stacked metal grains have a sufficient proportion in the metal layer, can ensure that the pressure bearing capacity of the current collector is effectively improved, that is, effectively improve the pressure bearing capacity of the current collector during the rolling process, and improve the use stability of the current collector. In addition, here, the area proportion of the staggered stacked metal grains in the metal layer can be tested and calculated according to the following operations: cut a longitudinal section of the metal layer every 5 meters, take more than 3 longitudinal sections for TEM characterization, calculate the area ratio of all staggered stacked metal grains in each longitudinal section of the metal layer to the area of the longitudinal section of the metal layer, and then take the average value. The size of each longitudinal section here is (1000~1500)×(800~1200)nm.
[0017] Preferably, the staggered stacked metal grains are evenly distributed in the metal layer. The staggered stacked metal grains are evenly distributed in the metal layer, which means that when the current collector is rolled, the pressure bearing capacity of each part of the current collector is relatively uniform, that is, each part can withstand a large pressure, so it is beneficial to improve the overall pressure bearing capacity of the current collector, and avoid the poor pressure bearing capacity of a certain part of the current collector, which leads to structural defects in the current collector, affecting the structural stability and service life of the current collector. And the uniform distribution is defined as: a longitudinal section of the metal layer is cut every 5 meters, and more than 5 longitudinal sections are taken for TEM characterization. By calculating the area ratio of the staggered stacked metal grains in the metal layer, among the more than 5 area ratios, (maximum value-minimum value) / maximum value <50%. The size of each longitudinal section here is (1000~1500)×(800~1200)nm.
[0018] Preferably, the current collector further comprises a substrate layer, and the metal layer is disposed on at least one side surface of the substrate layer.
[0019] Preferably, the substrate layer satisfies at least one of the following conditions: the thickness of the substrate layer is 1.0 to 10 μm; if the thickness of the substrate layer is too thin, the overall mechanical properties of the current collector will be reduced, its stability will be deteriorated, and the battery cycle performance will be deteriorated; and if the thickness of the substrate layer is too thick, the energy density of the battery will be reduced, which is not conducive to the improvement of the overall performance of the battery; the material of the substrate layer includes one or more of insulating polymer materials, metal materials, organic fiber materials, carbon materials, and inorganic materials, and the insulating polymer materials include polyethylene terephthalate, polypropylene, polybutylene terephthalate, polyethylene naphthalate, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene , polyphenylene sulfide, polyphenylene ether, polystyrene, polyimide, polyimide urea one or more; the metal material includes one or more of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum or tungsten; the organic fiber material includes one or more of polyacrylonitrile fiber, polyparaphenylene benzobisoxazole fiber, polybenzimidazole fiber, polyimide fiber; the carbon material includes one or more of conductive carbon black, acetylene black, natural graphite, artificial graphite, mesophase carbon microspheres, mesophase carbon fiber, vapor-grown carbon fiber, hard carbon, soft carbon, petroleum coke, graphene, fullerene, carbon nanotubes, glassy carbon; the inorganic material includes one or more of oxides, carbides, silicides, and nitrides. Preferably, the material of the substrate layer includes one or more of polyethylene terephthalate (PET), polypropylene (PP), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polyethylene (PE), polypropylene, polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS), polyphenylene oxide (PPO), polystyrene (PS), polyimide (PI), and polyimidurea (PASC).
[0020] Preferably, the metal layer satisfies at least one of the following conditions: (1) the thickness of the metal layer is 500 to 2000 nm; as a conductive layer, if the metal layer is too thin, the conductivity is poor; and if it is too thick, the prepared current collector is too thick and heavy, which is not conducive to improving the energy density of the battery; preferably, the thickness of the metal layer is 800 to 1200 nm; further, if the thickness of the metal layer is controlled within the above range, it is more beneficial to take into account the conductivity of the current collector and the energy density of the battery, and optimize the comprehensive performance of the battery; (2) the material of the metal layer includes one or more of aluminum, copper, silver, gold, nickel and their alloys; preferably, the material of the metal layer includes one or more of copper, aluminum and their alloys.
[0021] Preferably, a metal layer 1 and a metal layer 2 are respectively provided on both side surfaces of the substrate layer; the materials of the metal layer 1 and the metal layer 2 can be the same or different.
[0022] Preferably, the Young's modulus of the above-mentioned current collector is in the range of: >1600MPa. Controlling the Young's modulus to be larger can make the current collector have better mechanical properties, can further improve the structural stability of the current collector, and improve its pressure bearing capacity. The Young's modulus is controlled by adjusting the plasma bombardment parameters to control the degree of grain refinement or control the proportion of particles whose average length L of the grains in the Z direction satisfies the following relationship 0<L≤0.8K. Among them, the greater the ion bombardment intensity, the higher the degree of grain refinement, the greater the Young's modulus will be, and the higher the mass proportion of particles with 0<L≤0.8K, the greater the Young's modulus will be.
[0023] Preferably, the current collector further comprises a protective layer disposed on the surface of at least one metal layer. Adding the protective layer on the surface of the metal layer can prevent the metal layer from being chemically corroded or physically damaged, further improve the electrolyte resistance and mechanical properties of the current collector, and optimize the stability of the current collector.
[0024] Preferably, the protective layer satisfies at least one of the following conditions: (1) the thickness of the protective layer is 5 to 100 nm; if the protective layer is too thin, it cannot effectively protect the metal layer, which is not conducive to the battery charge and discharge cycle performance; if the protective layer is too thick, the battery energy density will be reduced; preferably, the thickness of the protective layer is 10 to 80 nm; further limiting the thickness of the protective layer within the above range is more conducive to taking into account the performance of the current collector and various aspects of the battery; (2) the material of the protective layer includes one or more of nickel, chromium, nickel-based alloys, copper-based alloys, copper oxide, aluminum oxide, silicon oxide, nickel oxide, chromium oxide, cobalt oxide, graphite, carbon black, copper chromate, copper chromite, carbon nano-quantum dots, carbon nanotubes, carbon nanofibers and graphene.
[0025] Preferably, the material of the protective layer is consistent or inconsistent; the thickness of the protective layer is consistent or inconsistent.
[0026] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned current collector, comprising the following steps: S1. placing a substrate layer in a vacuum evaporation chamber, melting and evaporating the metal material in the metal evaporation chamber at 1100-1600°C, allowing the evaporated metal atoms to diffuse to at least one side surface of the substrate layer, and cooling and depositing to form a metal layer on at least one side surface of the substrate layer; S2. performing plasma bombardment treatment on at least one side of the product obtained in S1 to obtain a current collector; the process conditions for the plasma bombardment treatment are: the gas source is an inert gas, the gas flow rate is 10-300mL / min, the working power is 1-20kW, and the treatment time is not less than 5s. In the preparation method of the current collector provided by the present invention, after depositing the metal layer on the two surfaces of the polymer film, the metal layer is subjected to plasma bombardment treatment using specific process conditions, so that the average length of the metal grains in the metal layer in the Z direction is effectively refined, thereby effectively improving the mechanical properties of the current collector in the Z direction, and making it less likely to produce defects during the pole piece rolling process, while maintaining a relatively high stability, which is beneficial to improving the stability of the current collector, the pole piece and the battery, and optimizing the battery charge and discharge cycle performance.
[0027] Preferably, in S2, the inert gas includes one or more of argon and helium.
[0028] Preferably, in S2, the processing time is 10 to 60 seconds.
[0029] Preferably, another method for preparing the above-mentioned current collector is provided, comprising the following steps: S1. placing the substrate layer in a vacuum evaporation chamber, melting and evaporating the metal material in the metal evaporation chamber at 1100-1600°C, allowing the evaporated metal atoms to diffuse to at least one side surface of the substrate layer, and cool and deposit to form a metal layer on at least one side surface of the substrate layer; S2. performing plasma bombardment treatment on at least one side surface of the product obtained in S1; the process conditions for the plasma bombardment treatment are: the gas source is an inert gas, the gas flow rate is 10-300mL / min, the working power is 1-20kW, and the treatment time is not less than 5s; S3. forming a protective layer on at least one side surface of the product in S2; the formation method includes one or more of physical vapor deposition, chemical vapor deposition, in-situ molding, coating and the like.
[0030] Preferably, the vapor deposition method includes one or more of vacuum evaporation and magnetron sputtering; the chemical vapor deposition includes one or more of atmospheric pressure chemical vapor deposition and plasma enhanced chemical vapor deposition; the coating method includes one or more of die coating, blade coating and extrusion coating.
[0031] According to a third aspect of the present invention, there is provided a pole piece, comprising the above-mentioned current collector or the current collector prepared by the above-mentioned preparation method and an electrode active material located on the current collector.
[0032] According to a fourth aspect of the present invention, a lithium battery cell is provided, comprising the above-mentioned pole piece.
[0033] According to a fifth aspect of the present invention, there is provided a battery pack comprising the above-mentioned lithium battery cell.
[0034] According to a sixth aspect of the present invention, there is provided an electrical device comprising the above-mentioned lithium battery cell or the above-mentioned battery pack.
[0035] In summary, the current collector provided in the present invention effectively improves the mechanical properties and conductivity of the current collector by controlling at least a portion of the metal layer in the current collector to contain staggered stacked metal grains, and the average length L of the metal grains in the Z direction and the thickness K of the metal layer satisfy the relationship 0<L≤0.8K, thereby further optimizing the charge and discharge cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is an electron microscope image of the aluminum metal layer after plasma bombardment treatment in Example 1 of the present invention.
[0037] Figure 2 This is an electron microscope image of the aluminum metal layer in Comparative Example 2 of the present invention before plasma bombardment treatment. DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.
[0039] Example 1
[0040] The current collector of this embodiment is prepared according to the following steps:
[0041] S1. Place a PET film with a thickness of 6 μm in a vacuum evaporation chamber, melt and evaporate high-purity aluminum wire (purity greater than 99.99%) in the metal evaporation chamber at 1300°C, diffuse the evaporated metal aluminum atoms to the two surfaces of the PET film, and cool and deposit on the two surfaces of the PET film under the cooling effect of the main roller to form two aluminum metal layers with a thickness of 1 μm;
[0042] S2. The product obtained in S1 was subjected to plasma bombardment treatment; the process conditions of the plasma bombardment treatment were: the gas source was argon gas, the gas flow rate was 100 mL / min, the operating power was 10 kW, and the treatment time was 30 s;
[0043] S3. The product obtained in S2 is placed in an oxygen atmosphere and oxidized for 2 minutes to form an aluminum oxide protective layer with a thickness of 5 nm on both surfaces of the product.
[0044] Example 2
[0045] It is basically the same as Example 1, except that in S2, the power of the plasma bombardment treatment process is 1 kW.
[0046] Example 3
[0047] It is basically the same as Example 1, except that in S2, the power of the plasma bombardment treatment process is 20 kW.
[0048] Example 4
[0049] It is basically the same as Example 1, except that: in S2, the processing time in the plasma bombardment treatment process is 5s.
[0050] Example 5
[0051] It is basically the same as Example 1, except that: in S2, the processing time in the plasma bombardment treatment process is 10s.
[0052] Example 6
[0053] It is basically the same as Example 1, except that: in S2, the processing time in the plasma bombardment treatment process is 60s.
[0054] Example 7
[0055] It is basically the same as Example 1, except that in S2, the argon gas flow rate in the plasma bombardment treatment process is 10 mL / min.
[0056] Example 8
[0057] It is basically the same as Example 1, except that in S2, the argon gas flow rate in the plasma bombardment treatment process is 300 mL / min.
[0058] Example 9
[0059] The method is basically the same as Example 1, except that the metal layer is a copper layer. The specific preparation process is as follows: a PET film with a thickness of 6 μm is placed in a vacuum evaporation chamber, and a high-purity copper wire (with a purity greater than 99.99%) in the metal evaporation chamber is melted and evaporated at 1500°C, so that the evaporated metal copper atoms diffuse to the two surfaces of the PET film, and under the cooling effect of the main roller, the two surfaces of the PET film are cooled and deposited to form a two-layer copper metal layer with a thickness of 1 μm.
[0060] Example 10
[0061] It is basically the same as Example 1, except that in S2, the power of the plasma bombardment treatment process is 21 kW.
[0062] Embodiment 11
[0063] It is basically the same as Example 1, except that in S2, the argon gas flow rate in the plasma bombardment treatment process is 310 mL / min.
[0064] Comparative Example 1
[0065] It is basically the same as Example 1, except that the power in the plasma bombardment treatment process is 0.8 kW.
[0066] Comparative Example 2
[0067] It is basically the same as Example 1, except that the plasma bombardment treatment in S2 is not performed.
[0068] Comparative Example 3
[0069] It is basically the same as Example 9, except that the plasma bombardment treatment in S2 is not performed.
[0070] Comparative Example 4
[0071] It is basically the same as Example 1, except that: in S2, the power in the plasma bombardment treatment process is 0.5 kW.
[0072] Comparative Example 5
[0073] It is basically the same as Example 1, except that: in S2, the processing time in the plasma bombardment treatment process is 3s.
[0074] Comparative Example 6
[0075] It is basically the same as Example 1, except that in S2, the argon gas flow rate in the plasma bombardment treatment process is 5 mL / min.
[0076] Test Case
[0077] 1. Experimental Construction Method
[0078] The average length of the grains in the Z direction, Young's modulus, surface roughness, square resistance and number of holes in the metal layer of the current collector prepared in all the above embodiments and comparative examples were tested. The specific testing method is as follows:
[0079] (1) Average length of grains in the Z direction of the metal layer: The average length of grains in the Z direction of the current collector metal layer was analyzed by combining a focused ion beam microscope (FIB-SEM) with a field emission transmission electron microscope (TEM). The specific method is as follows: the current collector sample is prepared according to the sample preparation requirements of the FIB, and then placed in the FIB FIB-SEM (Zeiss Gemini2 Crossbeam) for ion cutting of its cross section to prepare a cross-sectional sample with a thickness of about 50 nm. The prepared cross-sectional sample is placed in a TEM (JEM-2100F) for cross-sectional microstructure analysis (the cross-sectional size is (1000~1500)×(800~1200)nm). At the same time, the grains and their sizes are counted using the software supporting the TEM, and the average length of the metal grains in the metal layer in the Z direction is obtained after calculation.
[0080] (2) Young's modulus: It is used to characterize the mechanical properties of the current collector in the Z direction. The test method is as follows: the current collector is prepared according to the sample preparation method of atomic force microscopy (AFM), and then the sample is placed in AFM (Bruker-Dimension Icon), the sample surface is scanned, and the force between the probe and the sample surface is detected. The Young's modulus is calculated based on the force curve simulation.
[0081] (3) Surface roughness: A flat sample was placed on the sample stage of a surface roughness meter (Beijing Times TR260), and the surface of the sample was scanned with a probe to obtain the surface roughness Ra of the sample.
[0082] (4) Holes: The sample is placed in a surface quality detection system (micro-vision charge coupled device CCD), the surface is scanned, and then the optical signal is converted into an electrical signal and transmitted to a computer to count the number of holes on the surface of the current collector sample per unit area (per square meter).
[0083] (5) The area ratio of the misaligned stacked metal grains in the metal layer: Take a longitudinal section of the metal layer every 5 meters, take more than 3 longitudinal sections for TEM characterization, calculate the ratio of the area of all the misaligned stacked metal grains in each longitudinal section of the metal layer to the area of the longitudinal section of the metal layer, and then take the average value. Here, the size of each longitudinal section is (1000-1500)×(800-1200)nm.
[0084] 2. Experimental results
[0085] The test results of the current collectors prepared in all the above embodiments and comparative examples regarding the average length of the metal grains in the metal layer in the Z direction, Young's modulus, surface roughness, number of holes, and the area ratio of the staggered stacked metal grains in the metal layer are shown in Table 1.
[0086] Table 1 Test results of current collector related performance in the embodiments and comparative examples
[0087]
[0088]
[0089] As can be seen from Table 1 above, in the current collector provided by the present invention, the average length L of the metal grains in the Z direction in the metal layer is controlled within a certain smaller numerical range relative to the thickness of the metal layer, so that the current collector has relatively excellent mechanical properties and conductive properties. At the same time, the current collector can also take into account a good surface roughness, which is conducive to improving its adhesion with the electrode active material, improving the stability of the pole piece, and thus optimizing the battery cycle performance. In addition, the current collector can also take into account that there are fewer hole defects on its surface, so that it can maintain a higher stability during the charge and discharge cycle.
[0090] Further, it can be seen from Examples 1, 9 and Comparative Examples 2, 3 that: relative to conventional current collectors, the current collectors prepared by the present invention: a. have a smaller average length of metal grains in the metal layer in the Z direction, which is the result of the additional plasma post-treatment process to refine the metal layer grains; b. have a larger Young's modulus, that is, the mechanical properties in the Z direction are better, which is due to the refinement of the metal grains in the Z direction; c. have a higher surface roughness, which is caused by the bombardment of the metal layer surface by plasma, and a higher roughness is beneficial to the improvement of the bonding force between the current collector and the electrode active material during the subsequent preparation of the pole piece. d. In the longitudinal section of the metal layer, the area of the staggered stacked metal grains in the metal layer accounts for a higher proportion, which is beneficial to improving the mechanical properties of the current collector. Therefore, the current collector provided by the present invention has more excellent mechanical properties and conductive properties, and can improve the bonding force with the electrode active material, thereby effectively improving the mechanical properties, conductive properties and structural stability of the pole piece, which is beneficial to the current collector and the pole piece to maintain a high stability during the battery charge and discharge cycle, and is not easily damaged by cyclic stress, thereby improving the battery's cyclic charge and discharge performance. Further, from Figure 1 and Figure 2 It can be seen that Figure 1 This is an electron microscope image of the aluminum metal layer after plasma bombardment treatment in Example 1. Figure 2 This is an electron microscope image of the aluminum metal layer in Comparative Example 2 without plasma bombardment treatment. After plasma bombardment treatment, the average length of the metal grains in the metal layer in the Z direction is significantly and effectively reduced, thereby optimizing the mechanical properties and conductive properties of the current collector, and optimizing the battery cycle charge and discharge performance. It can also be seen from Example 1 and Comparative Example 2 that the plasma bombardment treatment is not performed in Comparative Example 2, resulting in a lower Young's modulus of the current collector, thereby causing the structural strength and stability of the current collector to be significantly reduced, and deteriorating the performance of the current collector.
[0091] From Examples 1-3, Example 10, and Comparative Examples 1 and 4, it can be seen that by increasing the power of plasma bombardment treatment, the prepared current collector: a. The average length of the metal grains in the metal layer in the Z direction is reduced, which is due to the increase in the energy of plasma post-treatment, which promotes the refinement of the grains; b. The Young's modulus is larger, that is, the mechanical properties in the Z direction are improved, which is due to the finer metal grains in the Z direction; c. The surface roughness is improved, which is due to the increase in the power of plasma post-treatment, which makes the plasma bombard the surface of the metal layer more intense. And it can be further seen that d. If the power of plasma bombardment treatment is too low, the performance improvement is not obvious, and if the power is too high, hole defects will appear on the surface; and if the power of plasma bombardment treatment is too low, it will also cause the area proportion of the misaligned stacked metal grains in the metal layer in the longitudinal section of the metal layer to decrease, which is not conducive to the improvement of the mechanical properties of the current collector.
[0092] It can be seen from Examples 1, 4-6 and Comparative Example 5 that by increasing the time of plasma bombardment treatment, the prepared current collector: a. The average size of the metal grains in the metal layer in the Z direction is reduced, which is because the extension of the plasma bombardment treatment time promotes the refinement of the grains; b. The Young's modulus is larger, that is, the mechanical properties in the Z direction are improved, which is due to the finer metal grains in the Z direction; c. The surface roughness is improved, which is because the increase in the plasma post-treatment time makes the plasma bombardment of the metal layer surface more intense; d. The post-treatment time is too short, resulting in a decrease in the area ratio of the staggered stacked metal grains in the metal layer in the longitudinal section of the metal layer, and the performance improvement is not obvious.
[0093] It can be seen from Examples 1, 7, 8, 10 and Comparative Example 6 that by increasing the post-treatment gas flow rate, the prepared current collector: a. The average size of the metal grains in the metal layer in the Z direction is reduced, which is due to the increase in the plasma post-treatment flow rate, which can increase the number of plasmas and promote the refinement of the grains; b. The Young's modulus is larger, that is, the mechanical properties in the Z direction are improved, which is due to the finer metal grains in the Z direction; c. The surface roughness is improved, which is due to the increase in the plasma post-treatment flow rate, which can increase the number of plasmas, thereby making the plasma bombardment of the metal layer surface more intense. And it can be further seen that d. The post-treatment gas flow rate is too low, the plasma generated is too low, and the area proportion of the misaligned stacked metal grains in the metal layer is reduced, resulting in no obvious performance improvement.
[0094] It can be further seen from Examples 1 to 11 and Comparative Examples 1, 4 to 6 that even after a certain plasma bombardment treatment, the area of the staggered stacked metal grains in the metal layer in Comparative Examples 1, 4 to 6 is relatively low, less than 20%. Compared with other embodiments, the Young's modulus of the current collectors in these comparative examples is lower, which means that their mechanical properties are relatively low, and therefore the overall performance of the current collectors is relatively low.
[0095] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A current collector, characterized in that: A metal layer is included, at least part of which includes staggered and stacked metal grains, and an average length L of the metal grains in the Z direction and a thickness K of the metal layer satisfy the following relationship: 0<L≤0.8K; The Z direction is the direction of the thickness of the metal layer.
2. The current collector according to any one of claims 1, characterized in that: At least a portion of the metal layer is filled with the metal grains in the Z direction.
3. The current collector according to claim 1, characterized in that: The metal layer is composed of staggered and stacked metal grains, the grain boundaries between the metal grains together form a continuous network structure, and the average length L of the metal grains in the Z direction and the thickness K of the metal layer satisfy the following relationship: 0<L≤0.8K; The Z direction is the direction of the thickness of the metal layer.
4. The current collector according to claim 1, characterized in that: In the longitudinal section of the metal layer, the area of the staggered and stacked metal grains in the metal layer accounts for ≥20%.
5. The current collector according to claim 1, characterized in that: The staggered and stacked metal grains are evenly distributed in the metal layer.
6. The current collector according to claim 1, characterized in that: The current collector further includes a substrate layer, and the metal layer is disposed on at least one side surface of the substrate layer.
7. The current collector according to claim 6, characterized in that: The substrate layer satisfies at least one of the following conditions: The thickness of the substrate layer is 1.0 to 10 μm; The material of the substrate layer includes one or more of insulating polymer materials, metal materials, organic fiber materials, carbon materials, and inorganic materials. The insulating polymer material includes one or more of polyethylene terephthalate, polypropylene, polybutylene terephthalate, polyethylene naphthalate, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide, polyphenylene oxide, polystyrene, polyimide, and polyimide urea; The metal material includes one or more of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum or tungsten; The organic fiber material includes one or more of polyacrylonitrile fiber, poly(p-phenylene benzobisoxazole) fiber, polybenzimidazole fiber, and polyimide fiber; The carbon material includes one or more of conductive carbon black, acetylene black, natural graphite, artificial graphite, mesophase carbon microspheres, mesophase carbon fibers, vapor-grown carbon fibers, hard carbon, soft carbon, petroleum coke, graphene, fullerene, carbon nanotubes, and glassy carbon; The inorganic material includes one or more of oxides, carbides, silicides, and nitrides.
8. The current collector according to claim 6 or 7, characterized in that: The material of the substrate layer includes one or more of polyethylene terephthalate, polypropylene, polybutylene terephthalate, polyethylene naphthalate, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide, polyphenylene oxide, polystyrene, polyimide, and polyimide urea.
9. The current collector according to claim 1, characterized in that: The metal layer satisfies at least one of the following conditions: (1) The thickness of the metal layer is 500 to 2000 nm; preferably, the thickness of the metal layer is 800 to 1200 nm; (2) The material of the metal layer includes one or more of aluminum, copper, silver, gold, nickel and alloys thereof; preferably, the material of the metal layer includes one or more of copper, aluminum and alloys thereof.
10. The current collector according to claim 9, characterized in that: A metal layer 1 and a metal layer 2 are respectively disposed on both side surfaces of the substrate layer, and the metal layer 1 and the metal layer 2 are made of different materials.
11. The current collector according to claim 10, characterized in that: The Young's modulus ranges from >1600 MPa.
12. The current collector according to claim 11, characterized in that: The current collector further includes a protective layer disposed on a surface of at least one of the metal layers.
13. The current collector according to claim 12, characterized in that: The protective layer satisfies at least one of the following conditions: (1) The thickness of the protective layer is 5 to 100 nm; preferably, the thickness of the protective layer is 10 to 80 nm; (2) The material of the protective layer includes one or more of nickel, chromium, nickel-based alloy, copper-based alloy, copper oxide, aluminum oxide, silicon oxide, nickel oxide, chromium oxide, cobalt oxide, graphite, carbon black, copper chromate, copper chromite, carbon nano-quantum dots, carbon nanotubes, carbon nanofibers and graphene.
14. A method for preparing a current collector according to any one of claims 1 to 11, characterized in that: The steps include: S1. placing the substrate layer in a vacuum evaporation chamber, melting and evaporating the metal material in the metal evaporation chamber at 1100-1600° C., diffusing the evaporated metal atoms to at least one side surface of the substrate layer, and cooling and depositing the metal atoms to form the metal layer on at least one side surface of the substrate layer; S2. Perform plasma bombardment treatment on at least one side of the product obtained in S1 to obtain the collector; the process conditions of the plasma bombardment treatment are: the gas source is an inert gas, the gas flow rate is 10 to 300 mL / min, the working power is 1 to 20 kW, and the treatment time is not less than 5 s.
15. A method for preparing the current collector according to any one of claims 12 to 13, characterized in that: The steps include: S1. placing the substrate layer in a vacuum evaporation chamber, melting and evaporating the metal material in the metal evaporation chamber at 1100-1600° C., diffusing the evaporated metal atoms to at least one side surface of the substrate layer, and cooling and depositing the metal atoms to form the metal layer on at least one side surface of the substrate layer; S2. Plasma bombardment treatment is performed on at least one side of the surface of the product obtained in S1; the process conditions of the plasma bombardment treatment are: the gas source is an inert gas, the gas flow rate is 10 to 300 mL / min, the operating power is 1 to 20 kW, and the treatment time is not less than 5 s; S3. Forming the protective layer on at least one side of the product in S2; the forming method includes one or more of physical vapor deposition, chemical vapor deposition, in-situ forming, coating and the like.
16. A pole piece, characterized in that: The invention comprises a current collector according to any one of claims 1 to 13 or a current collector prepared by the method according to any one of claims 14 to 15, and an electrode active material located on the current collector.
17. A lithium battery cell, characterized in that: Comprising the pole piece as claimed in claim 16.
18. A battery pack, characterized in that: Comprising a lithium battery cell as claimed in claim 17.
19. An electrical equipment, characterized in that: Comprising the lithium battery cell as claimed in claim 18 or the battery pack as claimed in claim 18.
Citation Information
Patent Citations
Current collector preparation method for in-situ generation of metal compound through plasma technology
CN112768624A
Negative electrode composite current collector, preparation method thereof and lithium ion battery
CN116666640A
Flexible composite positive electrode current collector with gradient multi-layer structure metal layer and preparation method of flexible composite positive electrode current collector
CN116895761A
Conductive film, preparation method thereof, composite current collector and lithium ion battery
CN117410496A
Current collector, preparation method thereof and application of current collector in lithium ion battery
CN117423836A
Cited By
Current collector and preparation method therefor
WO2026118643A1